Spin conversion of hydrogen using supported iron catalysts at cryogenic temperature - Das, Taraknath; Kweon, Soon-Cheol; Nah, In Wook; Karng, Sarng Woo; Choi, Jeong-Gil; Oh, In-Hwan (ELSEVIER SCI LTD, 2015)
Alumina-supported iron oxides have been prepared by incipient wetness impregnation method and employed for orthohydrogen to parahydrogen spin conversion at cryogenic temperature. These materials were characterized using a series of characterization techniques such as SEM, XRD, Raman and in situ FTIR spectroscopy. The spin conversion was investigated at low temperature by a batch mode of operation. The in situ FTIR spectra were collected in a transmission mode to obtain the spin conversion. While the iron oxide was highly dispersed over alumina support at low loading percent, a rodlike crystallite of iron oxide was formed at high loading percent. The 10 and 20 wt% iron oxides on alumina were proved to be the most active catalysts. The spin conversion process was very slow and time-dependent. It was concluded that the spin conversion was a function of various factors including the iron oxide loading percent, calcination temperature, and different supports. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: PARAHYDROGEN-INDUCED POLARIZATION; MATRIX-ISOLATION SPECTROSCOPY; PARA H-2 CONVERSION; LIQUID-HYDROGEN; VIBRATIONAL SPECTROSCOPY; MOLECULAR-HYDROGEN; OXIDE CATALYSTS; SOLID HYDROGEN; DRIFT SPECTRA; ZINC OXIDE